Implications of the geographical distribution of Shisha outlets for targeted tobacco control policies in Oman - Salma Al Kalbani (Eastern Mediterranean Health Journal, 2026)
Background: The availability and accessibility of Shisha strongly influence smoking behaviours, thus raising public health concerns and necessitating targeted interventions. Aim: To examine the geographic distribution of Shisha outlets in Oman and its implications for tobacco control policies. Methods: We obtained anonymised secondary data from the Oman Ministry of Economy on 1074 registered shisha outlets established across Oman's 11 governorates between January 2020 and October 2024. We analysed the data using SPSS version 27 and summarised it using frequencies and percentages. Results: Most of the outlets (97.1%) were Shisha cafés, with two-thirds (65.2%) in Muscat Governorate, followed by Dhofar (15.1%) and North Batinah (9.7%). Dhofar recorded a decrease in outlets from 16 in 2020 to 7 in 2024. Conclusion: The number of Shisha outlets in Oman increased during the 5-year period, thus increasing availability and accessibility. This widespread availability has the potential to normalize smoking behaviours and undermine tobacco control efforts. There is a need to strengthen zoning regulations, licensing, plain packaging, and health warnings to reduce availability and access.